Oxytocin Manipulation Alters Neural Activity in Response to Social Stimuli in Eusocial Naked Mole-Rats - Faykoo-Martinez, Mariela; Mooney, Skyler J.; Holmes, Melissa M. (Frontiers in Behavioral Neuroscience, 2018)
The social decision-making network (SDMN) is a conserved neural circuit that modulates a range of social behaviors via context-specific patterns of activation that may be controlled in part by oxytocinergic signaling. We have previously characterized oxytocin’s (OT) influence on prosociality in the naked mole-rat, a eusocial mammalian species, and its altered neural distribution between animals of differing social status. Here, we asked two questions: (1) do patterns of activation in the SDMN vary by social context and (2) is functional connectivity of the SDMN altered by OT manipulation? Adult subordinate naked mole-rats were exposed to one of three types of stimuli (three behavioral paradigms: familiar adult conspecific, unfamiliar adult conspecific, or familiar pups) while manipulating OT (three manipulations: saline, OT, or OT antagonist). Immediate early gene c-Fos activity was quantified using immunohistochemistry across SDMN regions. Network analyses indicated that the SDMN is conserved in naked mole-rats and functions in a context-dependent manner. Specific brain regions were recruited with each behavioral paradigm suggesting a role for the nucleus accumbens in social valence and sociosexual interaction, the prefrontal cortex in assessing/establishing social dominance, and the hippocampus in pup recognition. Furthermore, while OT manipulation was generally disruptive to coordinated neural activity, the specific effects were context-dependent supporting the hypothesis that oxytocinergic signaling promotes context appropriate social behaviors by modulating co-ordinated activity of the SDMN.